Changes in the protein content of Lamellidens marginalis from Jayakwadi dam at paithan during different seasons (M.S) India - Jadhav, Mangesh R; Jadhav, Jadhav N (International Multidisciplinary Research Journal, 2013)
In the present study, variation in the protein content in soft body tissues of Lamellidensmarginalis were collected from Jayakwadi dam, at Paithan near Aurangabad was observed during different seasons. As variation in the environmental conditions, it shown an effect on protein contents in the tissues like, mantle, hepatopancreas, gonad and foot. Protein content maximum found in gonads throughout all the three seasons, whereas mantle shows minimum values of protein. There are great fluctuations in the values of protein during different seasons.